In vitro fertilisation in patients with variant treatment for uterine fi broids (A Review) - Z. U. Archegova; N. K. Kasum-zade; R. I. Shalina (Кубанский научный медицинский вестник, 2020)
Background. Uterine fi broids is a highly prevalent gynaecological disease affecting 30–35% of reproductive age women and twice as many beyond this age, according to various sources. Uterine fi broids are diagnosed in 25–27% of infertile women. According to the American Society of Reproductive Medicine, this disease causes infertility in 2–3% of the cases.Objectives. A prognostic assessment of recovering fertility after treatment for uterine fi broids, outlining a comprehensive strategy for successful in vitro fertilisation after variant organ-preserving treatment for uterine fi broids.Мethods. Publication records were mined in the PubMed, Elibrary, Web of science and Cyberleninca databases under the search depth of 7 years. The query terms were: uterine fi broids, in vitro fertilisation, myomectomy, uterine artery embolisation, myomectomy and pregnancy, uterine artery embolisation and pregnancy, uterine fi broids and in vitro fertilisation.Results. We analysed 105 records and selected 32 for review. Many sources suggest that the putative pathogenetic mechanisms of a reduced in vitro fertilisation success in uterine fi broids comprise: abnormal circulation and receptor apparatus; abnormal uterine blood fl ow, venous stasis, vascular changes; local infl ammation; abnormal endometrial morphology, distortions of the uterine cavity with submucosal and large interstitial fi broids, continuity between endometrium and myometrium, subendometrial thickening; local nodal oestrogen/progesterone imbalance. Clinical data on the impact of uterine fi broids in assisted reproductive technology trials are multitude but ambiguous. Submucosal and intramural fi broids distorting the uterine cavity are commonly considered for resection due to their signifi cant negative impact on the pregnancy success rate with assisted reproductive strategies.Conclusion. Uterine fi broids pose an acute persistent challenge in gynaecology and reproductive medicine aggravated by the lack of a unifi ed strategy for patient management and reproductive life planning. Various aspects of the uterine blood fl ow diagnosis, treatment for uterine fi broids, pregravid preparation, long-term management of in vitro fertilisation protocols and pregnancy in this pathology require further detailed studies.